Gain Enhanced On-chip Monopole Antenna Utilizing Dual Rectangular Patch Artificial Magnetic Conductor at 5.8 GHz - Muhammad Abdullahi, Bello; Ain, Mohd Fadzil; Girgiri, Ahmadu; Mahmud, Mohd Nazri; Pakhuruddin, Mohd Zamir (International Journal of Integrated Engineering, 2025)
The rising popularity of chip-based wireless devices has incited greater attention in on-chip antenna (OCA) technology due to its compact size, low power consumption, and ease of integration into footprint chip-size transceivers. However, OCAs face challenges such as low gain, poor radiation efficiency, and a distorted radiation pattern due to the inherited low resistivity, and high permittivity lossy silicon substrate. This study introduces the dual-rectangular patch (DRP) structured artificial magnetic conductor (AMC) for the enhancing the performance of OCA. Thus, investigates the effect of the gain, and radiation efficiency of the proposed design. A DRP-AMC was developed as a modified AMC reflective surface, optimized to boost the gain and characteristic of the antenna at 5.8 GHz. To assess the design performance, the antenna prototype is fabricated and measured. As a result, an increase gain of 40.2% compared to the non-AMC-inspired model and 29.2% over the single-rectangular patch (SRP) model. This improvement is attributed to the DRP-AMC’s performance, making this antenna suitable for Wi-fi 6, RFID, and WiMAX applications at 5.8 GHz.